The Effect of Language Literacy and Numerical Literacy on the Result of the Minimum Competency Assessment (AKM) of SMAN Ploso Jombang - Dwi Wahyuni (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
Education is an attempt to master the knowledge from the formal or non-formal environment to create quality human resources. The results of a world assessment of education in Indonesia, according to the 2015 PISA report, is a world-class assessment program in which the academic performance of 15-year-old students shows that the development of education in Indonesia is still far behind compared to other countries in the world. Therefore the Ministry of Education and Culture has implemented a new program called the National Assessment as a substitute for the National Exam, which will be implemented in 2021. This study aims to determine the effect of language and numeracy literacy on the Minimum Competency Assessment (AKM) results. The method of collecting data in this study is through a questionnaire (questionnaire). Respondents taken in this study were 49 students of SMAN Ploso. Data analysis method using descriptive analysis. This study's results indicate an influence of language and numeracy literacy on the Minimum Competency Assessment (AKM) results. This can be proven by the t-test significance value of 0.067 > 0.05. Then the magnitude of the influence can be seen from the test results of the coefficient of determination with a value of 0.662 or 66.2% so that Ho is rejected and Ha is accepted, which means that the independent variables are proven to have a significant influence on the implementation of AKM which was held at SMAN Ploso Jombang. The implications of the data analysis results on reading and numeracy literacy with a minimum competency assessment, it is necessary to improve governance of learning and infrastructure so that the quality of school education can be achieved through holistic management and learning governance. The relation between reading and numeracy literacy is how the teacher presents material, and the use of learning media is the main thing that needs improvement. Using relevant learning media is urgently needed to support students' literacy skills at SMAN Ploso Jombang.